An integrated entrepreneurial performance model focusing on the importance and proficiency of competencies for start-up and established SMEs - M. Botha; J. J. van Vuuren; T. Kunene (South African Journal of Business Management, 2015)
Functional and enterprising competencies were identified in the integrated entrepreneurial performance model and the paper highlights which key skills and which supportive skills should be included in entrepreneurial training models and programmes. Functional competencies depend on business management/general business and technical skills. Enterprising competencies depend on entrepreneurial and personal skills. A clear distinction is made between general management and entrepreneurial skills. A multi-sample of 570 start-up and established small and medium enterprises (SMEs) was used to determine whether there are statistically significant differences between the groups in terms of the importance and proficiency in these competencies. Exploratory factor analysis was conducted to confirm the validity and reliability of the measuring instrument and several statistical tests, including t-tests and ANOVAs, were performed to test the hypotheses. Established SMEs considered functional competencies as being much more important than start-ups. This finding implies that start-up SMEs need to focus on the importance of functional competencies if they want to increase their chances of becoming established businesses. It was found that start-up, as well as established SMEs, consider enterprising competencies as important. The established group considered themselves very proficient in both the functional and enterprising competencies while the divergent was true for the start-up group.
Keywords: 650